Identification of nanoparticles and nanosystems in biological matrices with scanning probe microscopy. (17th April 2018) - Angeloni, Livia; Reggente, Melania; Passeri, Daniele; Natali, Marco; Rossi, Marco
Abstract : Identification of nanoparticles and nanosystems into cells and biological matrices is a hot research topic in nanobiotechnologies. Because of their capability to map physical properties (mechanical, electric, magnetic, chemical, or optical), several scanning probe microscopy based techniques have been proposed for the subsurface detection of nanomaterials in biological systems. In particular, atomic force microscopy (AFM) can be used to reveal stiff nanoparticles in cells and other soft biomaterials by probing the sample mechanical properties through the acquisition of local indentation curves or through the combination of ultrasound‐based methods, like contact resonance AFM (CR‐AFM) or scanning near field ultrasound holography. Magnetic force microscopy can detect magnetic nanoparticles and other magnetic (bio)materials in nonmagnetic biological samples, while electric force microscopy, conductive AFM, and Kelvin probe force microscopy can reveal buried nanomaterials on the basis of the differences between their electric properties and those of the surrounding matrices. Finally, scanning near field optical microscopy and tip‐enhanced Raman spectroscopy can visualize buried nanostructures on the basis of their optical and chemical properties. Despite at a still early stage, these methods are promising for detection of nanomaterials in biological systems as they could be truly noninvasive, would not require destructive and time‐consuming specific sample preparation, could be performed in vitro, on alive samples and in water or physiological environment, and by continuously imaging the same sample could be used to dynamically monitor the diffusion paths and interaction mechanisms of nanomaterials into cells and biological systems. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : By detecting nontopographical tip–sample interactions, scanning probe microscopy identifies nanoparticles buried in biological matrices.